(untitled) (Journal of Applied Learning and Teaching, 2019)
In this wide-ranging interview, we discuss continuities and watersheds of Professor Stephen Brookfield’s world-renowned and massive contributions to Higher Education and Adult Education. While Brookfield’s work demonstrates a remarkable continuity in terms of multi-angled perspectives on critical thinking and democratisation, there are also some notable changes through the years, such as a turn to self-directed learning (in the 1980s), a focus on power dynamics (in the 1990s), a theoretical turn (heavily influenced by Critical Theory, at the turn of the century) and a turn towards the importance of race relations (in the noughties). The extensive interview includes discussions of Brookfield’s four lenses (students’ eyes, colleagues’ perceptions, theory and personal experience); the power of failure; credibility and authenticity as key criteria of being a good teacher; the inevitable omnipresence of power and an open, pragmatic approach to learning and teaching methods; the importance of feedback and assessment’s key role as learning; use and abuse of technology in the classroom; MOOCs not being a disruptive innovation; Higher Education’s potential as an agent of liberation and prevailing counter-forces; how educational institutions can encourage skillful and critically-reflected teaching; and the connection between art and pedagogy. Since beginning his teaching career in 1970, Stephen Brookfield has worked in England, Canada, Australia, and the U.S., teaching in a variety of adult, community, organisational and higher education settings (the latter include Harvard University and Columbia University). In his endeavour to help adults learn to think critically about the dominant ideologies they have internalised, Professor Brookfield has written, co-written or edited 19 books on adult learning, teaching, critical thinking, discussion methods, critical theory and teaching race.